2014
DOI: 10.4103/0976-237x.132310
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of the efficacy of two controlled release devices: Chlorhexidine chips and indigenous curcumin based collagen as local drug delivery systems

Abstract: Aim:To comparatively evaluate the therapeutic efficacy of chlorhexidine (CHX) chips (Periocol-CG) and indigenous curcumin (CU) based collagen as adjuncts to scaling and root planning in the nonsurgical management of chronic periodontitis.Materials and Methods:A total of 120 sites from 60 patients presenting with chronic periodontitis (age group 25-55 years) of both sexes, with pocket depth of ≥5 mm with radiographic evidence of bilateral bone loss were earmarked for the study. A split mouth design was employed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 25 publications
0
22
0
7
Order By: Relevance
“…A comparative study was conducted to measure the therapeutic efficacy of chlorhexidine (CHX) chips and indigenous curcumin‐based collagen as adjuncts to scaling and root planing in the management of chronic periodontitis through nonsurgical procedures. At the end of a 6 month study period, a decrease in plaque and gingival index scores and improved microbiological parameters, probing pocket depth and clinical attachment levels were observed in both CHX chips and curcumin‐based collagen‐treated patients (Gottumukkala et al , ), indicating their beneficial therapeutic effects in the nonsurgical treatment of periodontal disease. Another study carried out by the same group of investigators indicated that 1% curcumin irrigation when used as an adjunct to scaling and root planing had a mild to moderate beneficiary effect (Gottumukkala et al , ).…”
Section: Clinical Studies With Curcuminmentioning
confidence: 98%
“…A comparative study was conducted to measure the therapeutic efficacy of chlorhexidine (CHX) chips and indigenous curcumin‐based collagen as adjuncts to scaling and root planing in the management of chronic periodontitis through nonsurgical procedures. At the end of a 6 month study period, a decrease in plaque and gingival index scores and improved microbiological parameters, probing pocket depth and clinical attachment levels were observed in both CHX chips and curcumin‐based collagen‐treated patients (Gottumukkala et al , ), indicating their beneficial therapeutic effects in the nonsurgical treatment of periodontal disease. Another study carried out by the same group of investigators indicated that 1% curcumin irrigation when used as an adjunct to scaling and root planing had a mild to moderate beneficiary effect (Gottumukkala et al , ).…”
Section: Clinical Studies With Curcuminmentioning
confidence: 98%
“…Among the multiple curcumin-formulations [15,21,102,103,104,105,106,107,108,109,110,111,112,113,114,115,116,117,118,119,120,121,122,123,124,125,126,127,128,129], the phytosomal formulation of CUR (Meriva), which is a complex of curcumin with phosphatidylcholine, is one of the well-studied curcumin-formulation (Table 1). Meriva is prepared by adding phospholipids to the hydroalcoholic extract of turmeric rhizomes under reflux conditions [21].…”
Section: Formulationsmentioning
confidence: 99%
“…Apart from Meriva and Theracurmin, several other CUR formulations have been reported in the literature [117,118,119,120,121,122,123,124,125,126,127,128,129]. Kakkar and Kaur reported a significant reduction in AlCl 3 related neurotoxicity in male lacca mice [117] using a solid lipid nanoparticle CUR formulation [117].…”
Section: Formulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the use of local antimicrobials, inserted directly on the pocket, can reach 100 times the concentration of the same drug administered orally ( Gottumukkala et al, 2014 ). Antimicrobials such as tetracycline, chlorhexidine (CHX), metronidazole ( Bansal et al, 2019 , Singh et al, 2018 ), 10% doxycycline, and 2% minocycline have been used as local drugs in periodontal disease treatment ( Singh et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%